KEKERASAN PADA TOKOH PEREMPUAN DALAM NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZY - Alimatussa'diyah Alimatussa'diyah (Asosiasi Dosen Muda Indonesia, 2023)
Violence has always been close to women. Violence experienced by women does not only occur in the real world, but also occurs in literary works. One of the literary works that describes violence against female characters is the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. In this research, it can be seen that the characterization of women in the novel Cinta Suci Zahrana is represented by Habiburrahman El Shirazy. Violence experienced by female characters. As well as feminist studies on female characters in the novel Cinta Suci Zahrana.